2010
DOI: 10.1016/j.otsr.2009.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Does hyperflex total knee design improve postoperative active flexion?

Abstract: Level 3, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
2
3
0
1
Order By: Relevance
“…However, they experienced a decrease in the mean maximum flexion they could achieve. This is similar to previous reports that Western patients with more than 120°of preoperative flexion experienced a decrease in flexion range [30,46]. There is a tendency for better postoperative flexion after TKA performed in Asian countries [5, 7, 8, 17, 18, 20, 24-26, 34, 40, 41, 43, 45, 50] than after TKA performed in Western countries [1,35,39,47,49] (Table 3).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, they experienced a decrease in the mean maximum flexion they could achieve. This is similar to previous reports that Western patients with more than 120°of preoperative flexion experienced a decrease in flexion range [30,46]. There is a tendency for better postoperative flexion after TKA performed in Asian countries [5, 7, 8, 17, 18, 20, 24-26, 34, 40, 41, 43, 45, 50] than after TKA performed in Western countries [1,35,39,47,49] (Table 3).…”
Section: Discussionsupporting
confidence: 90%
“…Student's paired t-tests were used to determine the difference between preoperative and postoperative values of all continuous outcome variables (HSS score, flexion contracture, maximum flexion, and ROM). To analyze the effects of the maximum postoperative flexion and the rate of achieving high flexion more than 135°, we grouped patients according to the maximum preoperative flexion (B 110°; 105°-115°; 120°-130°; C 135°), because this is known as a most predictable factor for postoperative flexion [28,37] and flexion gain may be different according to preoperative flexion [3,16,30]. To determine the knee survival for aseptic loosening, we used the life-table method for all patients [12].…”
Section: Methodsmentioning
confidence: 99%
“…인공 슬관절 디자인을 도입하여 안정성과 기능에서 기존의 인공 슬관절의 결과와 비슷하거나 더 우수하다는 결과가 많은 저자들 에 의해 보고되고 있다. 1,[3][4][5][6][7][8][9][10][11][12][13] 1). 17 Values are presented as median (range).…”
Section: 전재균·송인수·선두훈 외 2인unclassified
“…Our results are in contrast with another study using the same mobile-bearing high flexion design Rotating Platform Flexion (Sigma RPF), which concluded that preoperative flexion and the design of the knee prosthesis were the predominant factors of postoperative flexion. 26 But that study was most likely done in Caucasians. Another previous study also found that preoperative flexion played a significant role in the postoperative gain in flexion and not the type of prosthesis.…”
Section: Discussionmentioning
confidence: 99%